2017
DOI: 10.21475/ajcs.17.11.04.pne272
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of drought tolerance indices under different stress severities for bread wheat selection

Abstract: Drought is a world-wide spread problem adversely affecting bread wheat production in rainfed agro-ecosystems. Development and identification of efficient selection criteria for developing drought tolerant wheat varieties with stable and high yield potential is of paramount importance. This study was carried out to evaluate 24 indices for selecting the best high yielding and drought tolerant cultivars, among 40 bread wheat genotypes, under four levels of stress intensities: no stress, mild (0.25, 0.35) and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 24 publications
10
20
0
2
Order By: Relevance
“…This study revealed a decrease in mean grain yield of 34% in the drought-stressed main plot in which soil moisture declined to 50% field capacity level in the post flowering stage of the rice life cycle, relative to the unstressed main plot treatment in which irrigation ensured field capacity through until harvest. Decrease of grain yield due to drought stress in cereal crops has been reported previously by many workers (Rahman et al, 2002;Yue et al, 2006;Golabadi et al, 2006;Moosavi et al, 2008;Dadbakhsh et al, 2011;Farshadfar and Elyasi, 2012;Dixit et al, 2014;Bennani et al, 2017). The drought stress-induced grain yield reduction reported here was of moderate level.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This study revealed a decrease in mean grain yield of 34% in the drought-stressed main plot in which soil moisture declined to 50% field capacity level in the post flowering stage of the rice life cycle, relative to the unstressed main plot treatment in which irrigation ensured field capacity through until harvest. Decrease of grain yield due to drought stress in cereal crops has been reported previously by many workers (Rahman et al, 2002;Yue et al, 2006;Golabadi et al, 2006;Moosavi et al, 2008;Dadbakhsh et al, 2011;Farshadfar and Elyasi, 2012;Dixit et al, 2014;Bennani et al, 2017). The drought stress-induced grain yield reduction reported here was of moderate level.…”
Section: Discussionsupporting
confidence: 83%
“…Results in this study indicated a positive and highly significant correlation between YP and YS under moderate/0.34 stress level, suggesting that genotypes that showed high grain yield under non-stressed condition also demonstrated high yield under stressed condition. A positive correlation between YP and YS has also been reported in earlier studies (Moosavi et al, 2008;Dadbakhsh et al, 2011;Naghavi et al, 2013;Bennani et al, 2017). The drought indices STI, GMP, MRP, HARM, MP, REI and ATI also showed highly significant correlations with YP and YS, which suggests that the drought indices are able to identify high yielding genotypes under non-stressed and stressed conditions.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Substantial mean yield differences among genotypes under different irrigation levels indicate the presence of interaction effect of genotype by environment, where the expression of genes controlling tuber yield trait depends significantly on the genotype and water level condition. There was a significant difference in the overall mean tuber yield of all genotypes under no water stress (23.42 t ha -1 ) and water-stressed (7.08 t ha -1 ) conditions, which indicates a very high stress intensity ((1-(Ys/Yp)) (Bennani et al 2017) of 0.70 (within the range of 0.0-1.0). had also observed a dramatic difference of mean tuber yield of local sweet potato from NTT Province under normal and waterstressed conditions of 12.6 t ha -1 and 6.0 t ha -1 , respectively, with a stress intensity of about 0.5.…”
Section: Drought Tolerance Levelmentioning
confidence: 94%